(untitled) (Research, Society and Development, 2024)
Background: Low doses of different ketamine enantiomers have demonstrated rapid behavioural and biological actions in animals with depressive-like behavior. However, some authors report different effects depending on model of depression and ketamine isomer used. Objective: Our primary aim was to evaluate the effect of ketamine enantiomers on depressive-like behavior, anhedonic-like behavior and locomotor activity of rats subjected to maternal deprivation (MD). Secondarily, we investigated the Brain-derived neurotrophic factor plasma concentration between experimental groups. Methods: Male rats (n=71) were randomized into seven experimental groups: one non-deprived with placebo and other six deprived split into control and intervention groups. Rats were treated with a single intraperitoneal dose of ketamine, esketamine, or arketamine. One hour after drug application, we performed experimental tests to evaluate the antidepressant-like behavior and locomotor activity. Furthermore, blood was collected to measure plasmatic BDNF levels. Results: We did not observe induction of depressive-like in rats subjected to MD. Furthermore, there was no change in BDNF (F (6,64) = 0.9664, p=0.455) between all experimental groups. Conclusion: Neither MD nor the different ketamine isomers were able to change depressive-like behavior or plasma BDNF levels.